Book Review: Activity Theory, Authentic Learning and Emerging Technologies: Towards a Transformative Higher Education Pedagogy, V. Bozalek et al. (eds) - Van Der Merwe, Antoinette (Critical Studies in Teaching and Learning, 2023)
Book Review: Activity Theory, Authentic Learning and Emerging Technologies: Towards a Transformative Higher Education Pedagogy, V. Bozalek et al. (eds)